Spray drying of coffee leaf extract - Corrêa, Jefferson Luiz Gomes; de Mendonça, Kamilla Soares; Rodrigues, Leonardo Reis; Resende, Mário Lúcio Vilela; Alves, Guilherme Eurípedes (Coffee Science - ISSN 1984-3909, 2016)
The coffee leaf extract formulation has been used as resistance inductor in plants and to control phytopathologies. This work aimed to study the influence of spray drying process variables with the use of maltodextrin as carrier on the characteristics of the powder, by using a central composite rotational design (CCRD). The independent variables were maltodextrin concentration (X1, 0 to 30 % w/v), coffee leaf extract concentration (X2, 2 to 32 % w/v), inlet air temperature (X3, 180 to 250 °C) and air flow rate (X4, 3.5 to 5.5 m3min-1). The response variables were collection efficiency (h), moisture content (MC), phenolic compounds content (Ph), soluble solids (S) content, wettability (We) and particle size (Me). The results showed that the combination of a higher concentrations of coffee leaf extract (X2) (32%) and lower inlet air temperatures (X3) (180°C) make the best drying performance. This process condition lead to a powder with higher Ph, S, We, Me and lower MC. Therefore, the use of high air flow rates (X4) increase the collection efficiency (h) of process and the use of low maltodextrin concentration (X1) lead to better preservation of phenolic compounds content (Ph) on coffee leaf extract powdered.